2010
DOI: 10.1002/jcp.22300
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activity of TAp63 promoter is regulated by c‐jun

Abstract: The transcription factor p63 belongs to the p53 protein family and plays an important role in epithelial development. Recent studies showed that p63 is over-expressed in some human squamous cell carcinomas of the head and neck, suggesting a role in carcinogenesis. The p63 gene contains two promoters and alternative promoter usage generates two groups of proteins with (TAp63) or without (ΔNp63) the transactivation domain. Although the roles of TAp63 in epithelial development have been described in numerous rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…To understand how this agent suppresses or delays multiple types of degeneration in different paradigms, we initiated mechanistic studies to identify the targets of foretinib’s activity. Regarding die-back degeneration, we and others have previously described the major degenerative pathway in these neurons involving MKK kinases that activate JNK and its transcriptional target c-jun ( Kaplan and Miller, 2000 ; Culmsee and Mattson, 2005 ), the apoptotic p53 family member TAp63 ( Jacobs et al, 2005 ; Yao et al, 2010 ), and the Bax activators BimEL and Hrk ( Putcha et al, 2001 ; Towers et al, 2009 ), which in turn compromise mitochondria, culminating in cytochrome c release and activation of caspase-3 and caspase-6 and calpains ( Slee et al, 1999 ). Foretinib inhibited the expression, appearance, or activity of these proteins, all of which are necessary for neuronal death or axon degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To understand how this agent suppresses or delays multiple types of degeneration in different paradigms, we initiated mechanistic studies to identify the targets of foretinib’s activity. Regarding die-back degeneration, we and others have previously described the major degenerative pathway in these neurons involving MKK kinases that activate JNK and its transcriptional target c-jun ( Kaplan and Miller, 2000 ; Culmsee and Mattson, 2005 ), the apoptotic p53 family member TAp63 ( Jacobs et al, 2005 ; Yao et al, 2010 ), and the Bax activators BimEL and Hrk ( Putcha et al, 2001 ; Towers et al, 2009 ), which in turn compromise mitochondria, culminating in cytochrome c release and activation of caspase-3 and caspase-6 and calpains ( Slee et al, 1999 ). Foretinib inhibited the expression, appearance, or activity of these proteins, all of which are necessary for neuronal death or axon degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies also showed that the transcriptional activity of the TAp63 promoter and TAp63 protein level were both upregulated by an increased c-jun expression in Hep3B human hepatocellular carcinoma cell. [81] The elevated TAp63 expression was coincided with an increased binding of c-jun to the TAp63 promoter. Moreover, knockdown of TAp63 expression by shRNA led to an increased proliferation of Hep3B cell compared to that of the mock cell, suggesting a growth suppressive effect of TAp63 expression.…”
Section: P63 In Cancersmentioning
confidence: 95%
“…Moreover, knockdown of TAp63 expression by shRNA led to an increased proliferation of Hep3B cell compared to that of the mock cell, suggesting a growth suppressive effect of TAp63 expression. [81] Ectopic expression of p53 in p53-deficient cell (Hep3B) reduced TAp63 promoter activity and knockdown of TAp63 attenuated doxorubicin-induced cell growth arrest by promoting cell cycle progression via increasing the percentage of G2/M cells. [82] Moreover, knockdown of TAp63 increased cell sensitivity to doxorubicin-induced genomic damage.…”
Section: P63 In Cancersmentioning
confidence: 99%
“…The TAp63 knockdown in HepG2 and Hep3B hepatoma cells leads to increased proliferation and colony formation. TAp63 expression negatively correlates with tumor size, intrahepatic metastasis, and distant metastasis and, according to the results of a retrospective analysis, a low TAp63 level is associated with poor survival in HCC patients[ 85 , 86 ].…”
Section: Several Isoforms Of P53 Family Proteins Are Overexpressed Inmentioning
confidence: 99%